Force transducer system for measurement of ice hockey skating force - Stidwill, T. J.; Turcotte, R. A.; Dixon, P.; Pearsall, D. J. (Sports Engineering, 2009)
The purpose of this study was to develop a portable force measurement system for ice hockey skating. The system consisted of three strain gauge pairs affixed to an ice hockey skate`s blade holder with wire leads connected to a microprocessor controlled data acquisition device carried in a backpack worn by the skater. The configuration of the strain gauges simultaneously determined the vertical and medial-lateral force components experienced by the blade holder with a resolution accuracy of 1.9 N and a coefficient of variation of 9.2%. On-ice testing of this system with subjects performing forward start, acceleration, and constant velocity skating permitted unencumbered, natural movement and demonstrated clear, unambiguous signal responses, high trial-to-trial repeatability, and easy data retrieval. The practicality and accuracy of this testing approach have many applications, such as a quantitative tool for skating force assessment to aid athletes and coaches, as well as providing the means to examine other skill-specific dynamics.